Do colorectal cancer patients diagnosed as an emergency differ from non-emergency patients in their consultation patterns and symptoms? A longitudinal data-linkage study in England - Renzi, C (Br J Cancer, 2016)
BACKGROUND: More than 20% of colorectal cancers are diagnosed following an emergency presentation. We aimed to examine pre-diagnostic primary-care consultations and related symptoms comparing patients diagnosed as emergencies with those diagnosed through non-emergency routes. METHODS: Cohort study of colorectal cancers diagnosed in England 2005 and 2006 using cancer registration data individually linked to primary-care data (CPRD/GPRD), allowing a detailed analysis of clinical information referring to the 5-year pre-diagnostic period. RESULTS: Emergency diagnosis occurred in 35% and 15% of the 1029 colon and 577 rectal cancers. ‘Background' primary-care consultations (2–5 years before diagnosis) were similar for either group. In the year before diagnosis, >95% of emergency and non-emergency presenters had consulted their doctor, but emergency presenters had less frequently relevant symptoms (colon cancer: 48% vs 71% (P<0.001); rectal cancer: 49% vs 61% (P=0.043)). ‘Alarm' symptoms were recorded less frequently in emergency presenters (e.g., rectal bleeding: 9 vs 24% (P=0.002)). However, about 1/5 of emergency presenters (18 and 23% for colon and rectal cancers) had ‘alarm' symptoms the year before diagnosis. CONCLUSIONS: Emergency presenters have similar ‘background' consultation history as non-emergency presenters. Their tumours seem associated with less typical symptoms, however opportunities for earlier diagnosis might be present in a fifth of them.